Bituminous coal-based hard carbon negative electrode material for sodium ion battery and preparation method of bituminous coal-based hard carbon negative electrode material

Through preoxidation treatment and amino acid cross-linking technology, the graphitization of bituminous coal-based hard carbon materials is prevented, the layer spacing is expanded and the adsorption site is increased, which solves the problem of bituminous coal materials graphitization in sodium ion batteries, and improves the sodium storage capacity and electrochemical performance of hard carbon materials.

CN119873794APending Publication Date: 2025-04-25JIANGSU UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510100265.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In existing sodium ion batteries, bituminous coal-based hard carbon materials are prone to form graphitized structures during high-temperature conversion, resulting in too narrow layer spacing, hindering the insertion/extraction of sodium ions, and limiting their practical application in hard carbon anodes.

Method used

The rich oxygen-containing functional groups are introduced through pre-oxidation treatment and cross-linked with amino acids to construct a -C-(O)-O-(anhydride or ester group) group, preventing the graphitization of bituminous coal material, while increasing adsorption sites through N atom doping.

Benefits of technology

It effectively prevents the graphitization of bituminous coal materials, expands the layer spacing of hard carbon materials, increases sodium ion storage sites, and improves the sodium storage capacity and electrochemical properties of hard carbon materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873794A_ABST
    Figure CN119873794A_ABST
Patent Text Reader

Abstract

The invention discloses a bituminous coal-based hard carbon negative electrode material for a sodium-ion battery and a preparation method thereof, and the preparation method comprises the following steps: mixing and stirring bituminous coal powder and oxygen-containing acid or successively mixing and stirring the bituminous coal powder and the oxygen-containing acid and alkali, and carrying out oxygen-containing functional group grafting and de-ashing treatment; carrying out ball-milling mixing on the treated bituminous coal powder and amino acid powder; and carrying out segmented carbonization treatment on the mixed powder to obtain the bituminous coal-based hard carbon negative electrode material. The bituminous coal-based hard carbon prepared by the method provided by the invention realizes introduction of an N element and effective hindering of a graphitization process, forms rich carbon microcrystals, has large interlayer spacing and rich sodium ion adsorption sites, and the prepared hard carbon material has high reversible capacity and excellent cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a modified bituminous coal-based hard carbon material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries are considered a powerful alternative to lithium-ion batteries due to their low cost, abundant resources, safety and environmental protection. + ) has a radius larger than that of a lithium ion (Li + ), which makes it difficult to form a stable intercalation compound with graphite. Therefore, sodium-ion batteries cannot directly use commercially available graphite for lithium-ion batteries as negative electrode materials. In this context, hard carbon materials have become a hot topic in the research of negative electrode materials for sodium-ion batteries due to their unique structure and high sodium ion storage capacity.

[0003] Hard carbon is a carbon material that is difficult to graphitize, and it tends to develop in a short-range order during the high-temperature carbonization process. At present, the precursor raw materials of hard carbon materials mainly include biomass, resins, asphalt, etc. However, these precursors have problems such as unstable raw material supply, high prices and complex preparation processes, which limit the large-scale industrialization of hard carbon materials. In contrast, the carbon content of coal in hard carbon precursor materials is second only to graphite, and it is abundant in reserves and low in price. It is a very potential precursor raw material for preparing hard carbon materials. Bituminous coal is a medium-grade metamorphic coal. Compared with lignite, it has a low oxygen content and high reactivity, but it is easy to promote the orderly growth of carbon microcrystals to form a graphitic carbon structure during the carbonization process. This carbon rearrangement leads to too narrow interlayer spacing, hindering the insertion / extraction of sodium ions, and ultimately limiting its practical application in hard carbon anodes. Therefore, inhibiting the long-range graphitization of internal microcrystals in the high-temperature conversion process of bituminous coal is the key to using bituminous coal as a hard carbon negative electrode material for sodium ion batteries. Summary of the invention

[0004] Based on the technical problems existing in the prior art, the purpose of the present invention is to provide a bituminous coal-based hard carbon negative electrode material for sodium ion batteries, and a preparation method and use thereof. The present invention can improve the pre-oxidation efficiency of bituminous coal-based materials, enrich the -C-(O)-O- (anhydride or ester) groups, prevent bituminous coal from graphitizing during the carbonization process, expand the interlayer spacing of its pseudo-graphite domain, and perform N atom doping to increase the sodium ion adsorption sites, thereby improving the hard carbon capacity.

[0005] In a first aspect, the present invention provides a method for preparing a bituminous coal-based hard carbon negative electrode material, comprising the following steps:

[0006] S1: Mixing bituminous coal powder with oxygen-containing acid, or with oxygen-containing acid and alkali in sequence, and performing oxygen-containing functional group grafting and deashing treatment;

[0007] S2: ball milling the treated bituminous coal powder and the amino acid powder;

[0008] S3: The mixed powder is subjected to segmented carbonization treatment to obtain a bituminous coal-based hard carbon negative electrode material.

[0009] Preferably, the bituminous coal powder is obtained by crushing bituminous coal into powder and passing it through 100-200 meshes.

[0010] Preferably, the oxygen-containing acid is selected from one or more of concentrated sulfuric acid, nitric acid, and phosphoric acid; and the alkali is selected from one or both of sodium hydroxide and potassium hydroxide. The bituminous coal powder is acid-washed, or acid-washed and then alkaline-washed to deash until the ash content is less than 1%, and has abundant oxygen-containing functional groups. The deashing treatment can improve the sodium storage capacity of the hard carbon material.

[0011] Preferably, the amino acid is one or more of glycine, alanine, valine, leucine, serine and the like.

[0012] Preferably, the ball milling conditions are: a rotation speed of 200 to 500 r / min and a time of 1 to 5 hours. Under the mechanical force of the ball mill, the bituminous coal powder is fully mixed with the amino acid. If the ball milling speed is too low or the time is too short, the purpose of mixing cannot be achieved, and if the ball milling speed is too high or the time is too long, the structure of the material may be destroyed.

[0013] Preferably, the amino acid accounts for 10% to 40% of the total mass of the bituminous coal powder when ball-milled with the bituminous coal powder.

[0014] Preferably, the staged carbonization treatment is performed under an inert atmosphere or under nitrogen.

[0015] Preferably, the staged carbonization treatment refers to: the first stage: the carbonization temperature is 200-500°C, the heating rate is 2-10°C / min, and the insulation time is 1-5h; the second stage: the carbonization temperature is 1000-1600°C, the heating rate is 2-10°C / min, and the insulation time is 2-5h.

[0016] In a second aspect, the present invention further provides a bituminous coal-based hard carbon material prepared by the method described in the first aspect.

[0017] In a third aspect, the present invention further provides an application of a bituminous coal-based hard carbon material prepared by the method described in the first aspect in a negative electrode material for a sodium ion battery.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0019] 1) The present invention utilizes the strategy of pre-oxidation and amino acid cross-linking to directionally manufacture oxygen-containing functional groups that are beneficial to hindering the graphitization of bituminous coal. Oxidants such as concentrated sulfuric acid can make bituminous coal have abundant oxygen-containing functional groups (-OH, -COOH, -O-), etc. With these oxygen-containing functional groups as anchor points, carboxyl-rich amino acids can react with them by esterification or dehydration to construct abundant -C-(O)-O- groups, which can effectively prevent the rearrangement of bituminous coal materials during carbonization. Therefore, the interlayer spacing of the produced bituminous coal-based hard carbon is expanded, the sodium ion storage sites are increased, and the platform capacity is improved.

[0020] 2) In addition to cross-linking reaction to inhibit graphitization, the addition of amino acids also doped N atoms into the bituminous coal material, thereby increasing the capacity of the bituminous coal-based hard carbon material. N doping can provide more adsorption sites, which helps to increase the tilted capacity.

[0021] 3) The preparation process of the present invention is short, the process is simple, the cost is low, the practicability is good, and it is suitable for mass production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the SEM image of Example 1.

[0023] Figure 2 This is the XRD curve of the hard carbon material of Example 1.

[0024] Figure 3 These are the first charge and discharge curves of the hard carbon materials prepared in Example 1 and Comparative Example 1.

[0025] Figure 4 The charge and discharge cycle performance curves of the hard carbon materials prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is described in further detail.

[0027] Direct carbonization of bituminous coal-based materials is prone to generate graphitized structures, which is not conducive to their application in sodium ion batteries. The key to the present invention is to use methods such as grafting oxygen-containing functional groups and converting specific functional groups to hinder their graphitization, promote their transformation to hard carbon structure at high temperature, expand their interlayer spacing, and increase the adsorption sites by N doping, thereby improving the sodium storage capacity of hard carbon. Pre-oxidation introduces abundant oxygen-containing functional groups into the material. The cross-linking reaction of these functional groups can break the parallel overlap of the carbon layer and convert it from a two-dimensional structure to a three-dimensional structure, thereby hindering graphitization to a certain extent. Among these oxygen-containing functional groups, the presence of -C-(O)-O- (anhydride or ester group) groups promotes the formation of a three-dimensional cross-linked structure, effectively preventing the rearrangement of coal-based heavy carbon during the early pyrolysis process, thereby reducing the degree of graphitization. In order to increase the proportion of -C-(O)-O- groups in the functional groups of bituminous coal powder, we first use it to mix with oxygen-containing acid or with oxygen-containing acid and alkali in succession to make it have abundant carboxyl and hydroxyl sites, and then use amino acids with carboxyl groups to dehydrate or esterify them, cross-link them, and construct uniform and abundant -C-(O)-O- groups, which effectively prevent the rearrangement of carbon microcrystals during carbonization. The N in the amino acid is also incorporated into the bituminous coal during cross-linking, bringing more adsorption sites and larger interlayer spacing, effectively improving the hard carbon capacity of bituminous coal.

[0028] The present invention provides a method for preparing a bituminous coal-based hard carbon negative electrode material, the preparation method comprising the following steps:

[0029] (a) Crushing bituminous coal into bituminous coal powder of a certain particle size, and sieving the crushed bituminous coal powder using a 100-200 mesh screen. The purpose of this is to control the particle size and keep the particles uniform.

[0030] (b) A certain mass of bituminous coal powder is mixed and stirred with an oxygen-containing acid or with an oxygen-containing acid and an alkali at a certain temperature for 1 to 8 hours, and then washed with deionized water until it is neutral. The purpose of this is to oxidize and deash the bituminous coal powder, enrich its oxygen-containing functional groups, and remove the ash, which will affect the electrochemical properties of the hard carbon material.

[0031] (c) A certain mass of oxidatively deashed bituminous coal powder and amino acid powder is placed in a ball mill and milled for 1 to 5 hours at a speed of 200 to 500 r / min.

[0032] (d) placing the ball-milled powder in a tubular furnace, and in a protective atmosphere (argon or nitrogen), first heating the temperature to 200-500°C at a heating rate of 2-10°C / min for heat treatment for 1-5 hours, and then heating the temperature to 1000-1600°C at a heating rate of 2-10°C / min and carbonizing it for 2-5 hours to obtain a bituminous coal-based hard carbon material.

[0033] The present invention also provides a sodium ion battery using bituminous coal-based hard carbon prepared by the above method as a negative electrode material.

[0034] Battery assembly and testing: The performance of the bituminous coal-based hard carbon negative electrode materials prepared in the following examples and comparative examples was evaluated by button cells. The electrode slurry was prepared in the proportion of active material: conductive carbon black: binder CMC: dispersant SBR = 90:4:3:3. Appropriate amounts of ethanol and water were added to prepare the slurry, which was evenly coated on copper foil. After drying at 100°C for 12 hours, the electrode pieces were cut into pieces. The metal sodium sheet was used as the counter electrode, the electrolyte was 1M NaPF6 EC / DMC (1:1) solution, and the diaphragm was a glass fiber diaphragm GF / D, and assembled into 2032 button cells. At 0.025A g -1 The charge and discharge performance was tested under current density and voltage range of 0.001 to 2.5V.

[0035] Example 1

[0036] The method for preparing the bituminous coal-based hard carbon negative electrode material for a sodium ion battery of this embodiment comprises the following steps:

[0037] (a) washing the bituminous coal powder obtained after crushing and sieving with dilute nitric acid (5 mol / L) at 80° C. for 2 h, then washing with NaOH (5 mol / L) for 2 h for oxygen-containing functional group grafting and deashing, then washing with deionized water until neutral and drying;

[0038] (b) taking dried bituminous coal powder and alanine in a mass ratio of 7:1 and ball milling them in a ball mill for 3 h at a speed of 300 r / min;

[0039] (c) The ball-milled powder was placed in a tube furnace for staged carbonization, specifically: first, in an argon atmosphere, the temperature was raised to 400°C at a heating rate of 5°C / min for 2 h, then the temperature was raised to 1200°C at a heating rate of 5°C / min and carbonized for 2 h to obtain a bituminous coal-based hard carbon material, as shown in SEM. Figure 1 As shown, the XRD curve is Figure 2 As shown, the first charge and discharge curve and the charge and discharge cycle performance curve are shown as Figure 3 and Figure 4 shown.

[0040] The electrochemical performance results of the obtained bituminous coal-based hard carbon material are shown in Table 1.

[0041] Example 2

[0042] The other processes are the same as those in Example 1, except that: in step (a), during the oxygen-containing functional group grafting and deashing treatment, the washing with dilute nitric acid (5 mol / L) for 2 h and the washing with NaOH (5 mol / L) for 2 h are replaced by washing with a mixed solution of concentrated sulfuric acid (7 mol / L) and dilute nitric acid (5 mol / L) for 5 h.

[0043] The electrochemical performance results of the bituminous coal-based hard carbon material prepared in this example are shown in Table 1.

[0044] Example 3

[0045] The other processes are the same as those in Example 1, except that: in step (a), during the oxygen-containing functional group grafting and deashing treatment, the washing with dilute nitric acid (5 mol / L) for 2 h and the washing with NaOH (5 mol / L) for 2 h are replaced with washing with concentrated sulfuric acid (7 mol / L) for 5 h.

[0046] The electrochemical performance results of the bituminous coal-based hard carbon material prepared in this example are shown in Table 1.

[0047] Example 4

[0048] The other processes are the same as those in Example 1, except that in step (b), alanine is replaced by glycine.

[0049] The electrochemical performance results of the bituminous coal-based hard carbon material prepared in this example are shown in Table 1.

[0050] Example 5

[0051] The other processes are the same as those in Example 1, except that in step (b), alanine is replaced by valine.

[0052] The electrochemical performance results of the bituminous coal-based hard carbon material prepared in this example are shown in Table 1.

[0053] Example 6

[0054] The other processes are the same as those in Example 1, except that in step (b), alanine is replaced by leucine.

[0055] The electrochemical performance results of the bituminous coal-based hard carbon material prepared in this example are shown in Table 1.

[0056] Example 7

[0057] The other processes are the same as those in Example 1, except that in step (b), alanine is replaced by serine.

[0058] The electrochemical performance results of the bituminous coal-based hard carbon material prepared in this example are shown in Table 1.

[0059] Example 8

[0060] The other processes are the same as those in Example 1, except that in step (c), the heat treatment at 400°C for 2 h is changed to the heat treatment at 300°C for 2 h.

[0061] The electrochemical performance results of the bituminous coal-based hard carbon material prepared in this example are shown in Table 1.

[0062] Example 9

[0063] The other processes are the same as those in Example 1, except that in step (c), the heat treatment at 400°C for 2 h is changed to the heat treatment at 500°C for 2 h.

[0064] The electrochemical performance results of the bituminous coal-based hard carbon material prepared in this example are shown in Table 1.

[0065] Comparative Example 1

[0066] The other processes are the same as those in Example 1, except that in step (b), alanine is not added, and only the dried bituminous coal powder is ball-milled.

[0067] The first charge-discharge curve and the charge-discharge cycle performance curve of the bituminous coal-based hard carbon material prepared in this comparative example are shown in Figure 2. Figure 3 and Figure 4 The electrochemical performance results are shown in Table 1.

[0068] Comparative Example 2

[0069] The other processes are the same as those in Example 1, except that in step (a), no oxygen-containing functional group grafting is performed and only deashing is performed, that is, the bituminous coal powder obtained after crushing and sieving is washed with dilute hydrochloric acid (5 mol / L) at 80° C. for 5 h.

[0070] The electrochemical performance results of the bituminous coal-based hard carbon material prepared in this comparative example are shown in Table 1.

[0071] Comparative Example 3

[0072] The other processes are the same as those in Example 1, except that in step (c), no segmented carbonization is performed, that is, the temperature is raised to 1200° C. at a heating rate of 5° C. / min under an argon atmosphere and then carbonized for 2 h.

[0073] The electrochemical performance results of the bituminous coal-based hard carbon material prepared in this comparative example are shown in Table 1.

[0074] Table 1 Performance of bituminous coal-based hard carbon negative electrode materials prepared in various embodiments and comparative examples

[0075]

[0076]

[0077] It can be seen from the data in Table 1 that the performance of Examples 1, 2, and 3 is improved compared to the blank control Example 2 that has not been washed with oxygen-containing acid, especially Example 1. This is because the oxygen-containing acid washing provides enough oxygen-containing functional groups for the bituminous coal powder, which hinders the graphitization of the bituminous coal powder during the carbonization process, expands the interlayer spacing, and is beneficial to the storage of sodium ions. The performance of Examples 1, 4, 5, 6, and 7 is improved compared to the blank control Example 1 without the addition of amino acids. This is because amino acids have carboxyl groups and amino groups. The carboxyl groups can undergo dehydration or esterification reactions with oxygen-containing functional groups to effectively generate acid anhydrides or ester groups. The presence of this functional group promotes the formation of a three-dimensional cross-linked structure, thereby hindering graphitization during the carbonization process. The N in the amino group is also incorporated into the hard carbon, increasing the sodium adsorption sites, which is beneficial to the storage of sodium ions. It can be seen from the data of Examples 1, 8, 9 and Comparative Example 3 that the performance of Examples 1, 8, 9 is improved compared to Comparative Example 3 which has not undergone low-temperature heat treatment. This is because Comparative Example 3 has not undergone a pre-oxidation process, and the oxygen-containing functional groups do not have sufficient conditions to undergo a cross-linking reaction, and cannot break the parallel overlap of the carbon layers, thereby being unable to hinder graphitization. The smaller interlayer spacing is not conducive to sodium ion storage.

Claims

1. A method for preparing a bituminous coal-based hard carbon negative electrode material, characterized in that: The steps include: S1: Mixing bituminous coal powder with oxygen-containing acid, or with oxygen-containing acid and alkali in sequence, and performing oxygen-containing functional group grafting and deashing treatment; S2: ball milling the treated bituminous coal powder and the amino acid powder; S3: The mixed powder is subjected to segmented carbonization treatment to obtain a bituminous coal-based hard carbon negative electrode material.

2. The method according to claim 1, characterized in that Bituminous coal powder is obtained by crushing bituminous coal into powder and passing it through 100~200 mesh.

3. The method according to claim 1, characterized in that The oxygen-containing acid is selected from one or more of concentrated sulfuric acid, nitric acid and phosphoric acid; the alkali is selected from one or both of sodium hydroxide and potassium hydroxide.

4. The method according to claim 1, characterized in that The amino acid is one or more of glycine, alanine, valine, leucine and serine.

5. The method according to claim 1, characterized in that The ball milling conditions are: a rotation speed of 200-500 r / min and a time of 1-5 h.

6. The method according to claim 1, characterized in that When the amino acid is ball-milled with the bituminous coal powder, it accounts for 10% to 40% of the total mass of the two.

7. The method according to claim 1, characterized in that The staged carbonization treatment needs to be carried out under an inert atmosphere or nitrogen.

8. The method according to claim 1, characterized in that The staged carbonization treatment refers to: the first stage: the carbonization temperature is 200-500 °C, the heating rate is 2-10 °C / min, and the holding time is 1-5 h; The second stage: carbonization temperature is 1000~1600℃, heating rate is 2~10℃ / min, and holding time is 2~5h.

9. A bituminous coal-based hard carbon material prepared by the method according to any one of claims 1 to 8.

10. Use of a bituminous coal-based hard carbon material prepared by the method according to any one of claims 1 to 8 in a negative electrode material for a sodium ion battery.

Citation Information

Cited By

  • Method for preparing coal-based hard carbon by enhancing coal oxidation reaction activity

    CN120757102A

  • Preparation method of coal-based hard carbon negative electrode material for sodium electricity

    CN121405067A